PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA DALAM PERJANJIAN KERJA WAKTU TERTENTU PADA PERUSAHAAN GARMEN - Ita Rosita (Magister Hukum Sekolah Pascasarjana Unida, 2016)
Today many companies use labor through Work Agreement of Specific Time (PKWT) to reduce the labor cost in order to increase profits. But in the execution, many applications of the work agreement of specific time were not in accordance with the provisions in the Law No. 13 Year 2003 about Manpower that ultimately disadvantaging the labor. This research aims to know legal protection of labor in the implementation of work agreement of specific time at a garment company in Sukabumi. Research methods used by the author in this research are normative judicial and empirical judicial methods. The findings suggest that first, the implementation of work agreement between the labor and the company is not according to the Law No. 13 Year 2003 especially on Article 59 about job assignment. Second, the implementation of legal protection at the company on the welfare of the labor is acceptable although is not satisfying yet. Third, promotion of labor of specific time to become full time employee at the company is based on performance. Labor of specific time that was considered having good achievement, discipline and able to work together with other workers could be promoted to become full time employee.